(3OjhGf YeQ Hf CHj QHjYIs - (3GHf CHj QHjYI , YeQ Hf YHO Gddg Hf CHj QHjYI GdeNRhej, CHh GdNWGH,J (B93 (3g` s ((3eMeO Hf YHOGdQMef Hf CMeO Hf eMeO GdTgjQ HGHf OLGL s)
(3ChdgG (B:s
(3bGd GHhGdMSf GdeOGFfj(B: (3CJi YeQ Hf CHj QHjYI GdhdjO Hf YHOGdedc abGd ef CfJ? abGd YeQ Hf CHj QHjYI bGd GdTGYQ, hbGd(B: (3Ef eKdj dG jfSH Edi TYQ s
(3BNQgG (B:s
(3hCZQ cGdGZQjV YPH de jaQg GfJbGUg Je GdOjhGf HMeO Gdedc GdOjGf s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B211s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B165 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B803s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs